Mechanicals properties from three thermo-activated titanium-nickel orthodontic archwire brands. In vitro Study - Ramos Torres, Viviana (2010)
The optimal selection of orthodontic archwires allows the professional to make the treatment in an efficient way; therefore, the knowledge of basic mechanical properties is required, which are not revealed by their manufacturers. The purpose of this study was to compare the mechanical properties (constant tension in the activation area, constant elongation in the activation area, maximum resistance and break point) of three thermo-activated titanium-nickel orthodontic archwires. 10 0.4 mm-diameter thermo-activated titaniumnickel orthodontic archwires from the following brands were used: NiTi GACR (Control Group), Nitinol Termoactivado 3M UnitekR, Sentalloy GACR, Nitinol Termoactivado TECNIDENTR. 80 mm test bodies were prepared and tested for traction using a Zwick / Roell machine model Z050 8402 with a 50 kN capacity, at a speed of 1 mm/min and at 37 °C. The results show that the higher value was obtained by Nitinol 3M Unitek (374,43 + 16,72 MPa) for the constant tension in the activation area, while the Nitinol Tecnident showed the higher value (14,51 + 0,91%) in the constant elongation in the activation area. The Nitinol Sentalloy GAC recorded the higher value in the maximum resistance (1398,59 + 45,36 MPa) and break point (174,29 + 6,47 N). It was concluded that the thermo-activated titanium-nickel orthodontic archwires present differences in their mechanical properties.